Cartazes circulantes: Atores, instituições e ambientes de manifestações midiatizadas - Neves, Manoella Maria Pinto Moreira das (Universidade do Vale do Rio dos Sinos, 2017)
The poster, in the society in the process of mediatization, detaches itself even more from the physical support of the cardboard and shows itself as an element of entry and performance in the contemporary manifestations occurring in Brazil and in the world. In this thesis, the poster studied is the one used and appropriate in recent manifestations, most punctually in June 2013, in Brazil. In the ambiences where it passes, the poster is adapted and registered according to the techniques, rules and intentions of each space: street / square - digital social networks / virtual space - traditional media / audience. Being physical support, being image, being posted or its content being transformed into hashtag, the ambiences are marked in the passage of the poster. And, in addition to being a physical medium, the poster contains a message consisting of interaction and circulation. Managing the circulation, the senses circulate and the poster appears as a circulating sign. The thesis is, in this sense, an effort to register understanding about discursive circulation and mediated ambiences of this circulation. The work is theoretically referenced from authors who deal with the topic of mediatization and its logics, circulation, flows and ambiences, in particular, some of the professors who give support to Research Line 4 of the Program of which this research is inscribed are: Ferreira (2006, 2007, 2012, 2013, 2016), Braga (2013, 2012, 2011, 2010, 2007, 2006), Fausto Neto (2015, 2010, 2008) e Rosa (2014, 2012).. Faced with the need to highlight the poster, Moles (2004) was specially the reference. The question Semiotics that runs through the research is based on Peirce (2007,2005) and Bakhtin (1997,1992), from which their conceptions approach, namely, the value of the sign beyond the object it represents and that at the same time contains it - this approximation was possible through Santaella (1994) and Santaella and Nörth (2004). Véron (2013, 2005, 1997) is the author who allows the relation between semiotics and circulation. And by Mata (1992) are outlined the spaces of ambience of the circulation of the poster. Thus, the theoretical and methodological pretension of this thesis is to register a social experience of production of circuits of circulation and marking of mediatized ambiences, from the use and appropriation of the poster in the Manifestations of June of 2013, in Brazil.
Keywords: Midiatização; Circulação discursiva; Ambiências; Cartaz; Manifestação; Midiatization; Discursive circulation; Ambiences; Poster; Manifestation; ACCNPQ::Ciências Sociais Aplicadas::Comunicação